Analisis Keterampilan Teknik Dasar Futsal Pemain Futsal Putri Padang Futsal Akademi (PFA) Kota Padang - Selvi Yolanda; Ridho Bahtra (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
The problem in this study is that the basic technical skills of the players have not been described. The purpose of this study was to determine the basic technical skills of women's futsal players at the Padang Futsal Academy (PFA). This type of research is descriptive research. The population in this study were all female Padang Futsal Academy (PFA) players, totaling 20 people. The sampling technique uses a total sampling technique so that the sample in this study is 20 people. The instrument used is a futsal skills test consisting of passing-control, dribbling, and shooting. The data analysis technique uses frequency distribution. Data were analyzed using the 5A scale formula in 5 categories, namely: very good, good, enough, less, and very less. Based on the results of the basic skills test for playing futsal on 20 people, it was found that 2 people (10%) had a very good category, 2 people (10%) had a good category, 9 people (45%) had an adequate category and 7 people (35%) had a very poor category. ). Thus, it can be concluded that the basic technical skills of the Padang Futsal Akademi women's futsal players are in the enough category.